Chronic foreign body aspiration in a Saudi Child - An occult cause of chronic pulmonary disease: Case report and literature review - Mai S Al-Zahrani (Saudi Journal of Medicine and Medical Sciences, 2015)
This case report describes an 8-year-old female, who presented with repeated chest infections. She was screened for acid fast bacilli, immune deficiency syndrome, and cystic fibrosis. The computed tomography scan revealed collapsed left upper lobe with multiple cystic lesions in the lingula. Bronchoscopy was performed, and a foreign body was removed. This diagnosis is still considered a missed and an overlooked (forgotten) diagnosis.